UNNES Goes Conservation: Among Students’ Knowledge, Perception and Attitude of Students’ Environmental Conservation - Dyah Rahmawati, Fentya; Tusyanah, Tusyanah; Citra Dewi, Lita; Rachmawati Indira, Fransisca (KnE Social Sciences, 2020)
UNNES has a vision of becoming a conservation-oriented and internationally reputed university. It makes UNNES carries out the policies to aware and to implement the conservation values. There are 8 (eight) pillars of conservation; however, the study focuses on 5 (five) pillars which are directly on the environment. The other 3 (three) pillars relate to the culture and character conservation. The objective of the study is to understand the real condition of Students’ Environmental Conservation after implementing some conservation programs and policies conducted by UNNES. It is quantitative research taking students from UNNES (UNNES) as the population. The total population was 24,000 students and with Slovin formula; there were 393 students as the samples. Data were collected by distributing the questionnaires with 3 (three) variables; knowledge, perception, and attitudes of UNNES students on environmental conservation. Then the data were analyzed descriptively and inferentially. All data were processed using SPSS 23.5 for Windows. The results of the study showed which; 1) 52% of respondents have high knowledge on Environmental Conservation; 2) 50% of the respondents have very high perception on Environmental Conservation; 3) 61% of respondents have good attitude on Environmental Conservation; and 4) simultaneously; Knowledge students (X1) and students’ perception (X2) have effects for 66.5% on their attitudes on environmental conservation (Y). Next, the partial results of students’ knowledge (X1) had an effect for 35.9% on their attitudes on environmental conservation (Y) and students’ perception (X2) had an effect for 61.3% on their attitudes on environmental conservation (Y). It means that students already have good environmental knowledge, perception and attitudes on conservation. It is suggested to improve students’ attitudes on conservation by improving their knowledge and perception. Keywords: Knowledge, Perception, Attitude, Environmental Conservation